The Role of Employer Brand Attractiveness in Attracting Generation Z's Interest in Applying to Startup Companies - Kesumahurip, Ade Wedhar Puji; Paramanda, Nyoman Putri Vidya; Pramusiwi, Aloysia Desy (Sharia Business Management UIN Raden Intan Lampung, 2025)
In this era of intense business competition, having quality human resources is critical to company success. To have quality human resources, employer brand attractiveness becomes crucial in attracting the intention of applying for prospective employees, especially Generation Z. There are five dimensions in employer brand attractiveness: value of interest, social value, economic value, development value, and value of cooperation. There are five dimensions of employer brand attractiveness: value of interest, social value, economic value, development value, and value of collaboration. This study examines each dimension of employer brand attractiveness on the intention to apply for prospective employees, especially Generation Z in startup companies. Purposive sampling was used for this research survey, and 125 Generation Z respondents who live in Yogyakarta were obtained. SEM analyzed data with Smart PLS. The results of this study show that social value and economic value do not affect the intention to apply to startup companies in Generation Z, while the value of interest, development value, and value of cooperation affect the intention to apply to startup companies in Generation Z.